2017
DOI: 10.1111/cote.12321
|View full text |Cite
|
Sign up to set email alerts
|

Structural, spectroscopic and computational study of 5‐(substituted phenylazo)‐3‐cyano‐1‐ethyl‐6‐hydroxy‐4‐methyl‐2‐pyridones

Abstract: Ten 5-(substituted phenylazo)-3-cyano-1-ethyl-6-hydroxy-4-methyl-2-pyridones were studied (five new compounds) to provide insight into the electronic effects of diverse substituents located at different positions in their phenyl moieties. The structural features of these dyes were examined by combining experimental and theoretical approaches. The crystal structures of two derivatives were revealed by X-ray crystallography and diverse packing modes owing to different intermolecular interactions (p-p stacking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The obtained absorption spectra suggest the existence of hydrazone tautomeric form in case of all investigated dyes[16][17][18]41,42].…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…The obtained absorption spectra suggest the existence of hydrazone tautomeric form in case of all investigated dyes[16][17][18]41,42].…”
mentioning
confidence: 69%
“…However, the existence of hydrazone form is confirmed by NMR analysis in CF3COOD solution. The signal of low intensity at 15.03 ppm, in 1 H NMR spectrum, was ascribed to the N-H proton resonance of the hydrazone -NH group [41], and signal at 128.32 ppm, in 13 C NMR spectrum, was ascribed to C5=N.…”
Section: Synthesismentioning
confidence: 99%
“…It can be observed that two absorptions of different intensity appear in the experimental UV–Vis spectrum in this solvent. According to the literature, the origin of this may be attributed to the acid–base equilibrium , that is, the presence of hydrazone and anionic forms (Scheme ). In order to determine the position of the UV–Vis maximum for the pure hydrazone tautomeric form in DMSO, hydrogen chloride is added dropwise to this solution, and the UV–Vis spectrum is presented in Figure , along with the experimental spectrum of DAPD in DMSO (before adding hydrogen chloride), and the scaled calculated spectra of the hydrazone and anionic forms.…”
Section: Resultsmentioning
confidence: 99%
“…The new TM complexes were synthesized in the reaction of azo pyridone dyes 1 and 2 with Cu(CH 3 COO) 2 ⋅H 2 O in DMF at room temperature (Scheme 1). Dyes ( 1 and 2 ), used as ligands in the synthesis, were fully characterized in our previous studies 36,37 . X‐ray crystallography analysis of the dyes confirmed the existence of the hydrazone form in the solid state (as depicted in Scheme 1).…”
Section: Resultsmentioning
confidence: 83%
“…Dyes 1 and 2 , used as ligands for the synthesis of the complexes, were previously synthesized and characterized 36,37 . Cu (CH 3 COO) 2 ⋅H 2 O (0.0093 g, 0.0467 mmol) was dissolved in 10 mL of DMF and added dropwise to the DMF solution (10 mL) of each dye (0.0934 mmol).…”
Section: Methodsmentioning
confidence: 99%